ASSESSMENT OF URINARY 8-HYDROXYDEOXYGUANOSINE LEVEL IN DIABETIC CANCER PATIENTS - (:unkn) unknown (INT JOURNAL PHARMACEUTICAL SCIENCES & RESEARCH, 2017)
Both diabetes mellitus and cancer are characterised by higher levels of oxidative stress and production of free radicals, which further complicate the control and outcomes of these diseases. The aim of this study was to assess the level of urinary 8-Hydroxydeoxyguanosine in diabetic cancer patients as a biomarker of cellular oxidative stress for both disease progression and chemotherapy administration. A controlled prospective observational study carried out on 100 diabetic patients newly diagnosed with diverse cancer types eligible for different chemotherapeutic protocols at the oncology unit. Urinary 8-Hydroxydeoxyguanosine level assessed at the baseline (before the required chemotherapy protocol schedule), and the 2nd reading (at the end of the required chemotherapy protocol schedule). Results showed that there was a significant (p<0.05) increase the urinary 8-Hydroxydeoxyguanosine level between the baseline and 2nd readings (27.04 +/- 4.33 ng/dl) vs (30.77 +/- 4.63ng/dl), and between the baseline and 2nd readings at 7-day course (25.96 +/- 4.21ng/dl) vs (28.16 +/- 5.27ng/dl), at 14-day course (27.76 +/- 5.33 ng/dl) vs (31.56 +/- 4.47ng/dl), and at 21-day course (27.22 +/- 4.16 ng/dl) vs (31.40 +/- 4.24ng/dl). In conclusion, this study presented that oxidative stress based on elevation of the urinary 8-OHdG level is related to diabetes mellitus and cancer which is further boosted during chemotherapy administration.
Keywords: Oxidative stress; Urinary 8-OHdG; Diabetes Mellitus; Cancer; OXIDATIVE STRESS; INSULIN-RESISTANCE; MELLITUS; DNA; BIOMARKER; LINKS